Diversifikasi Buah Kelapa (Cocos nucifera L.) sebagai Nilai Tambah Pendapatan Usahatani Kelapa di Lahan Pasang Surut - Wiwin Novita Sari; Mustofa Marli Batubara; Khaidir Sobri (Jurnal Lahan Suboptimal : Journal of Suboptimal Lands, 2015)
This study aims to determine the processes implemented coconut diversification as value added of coconut farms income the area of tidal land in Banyuasin and find out how much value added of coconut farm income. The population as an example 7 respondents used was a survey method. Data collection methods used in this study were interviews with coconut farmers using a prepared list of questions and the data obtained from the relevant institutions that have anything to do with the study, analyzed the tabulation. Develoving a diversification of Coconut farm in addition to provide value-added farm income, it is expected to grow jobs and boost economic growth in rural areas. Based on the research results and the discussion indicated that the diversification process in the form of a sort the results coconuts meat, charcoal, coir and coconut water. Coconut farm income of Rp 9.413.974,00/year, coconut diversification income Rp 9.951.400,00/year. Value-added diversification of Rp 805.94 coconut/fruit